Assessment of Hepatotoxic Potential of Cyanobacterial Toxins Using 3D In Vitro Model of Adult Human Liver Stem Cells - Basu, Amrita; Dydowiczová, Aneta; Čtveráčková, Lucie; Jaša, Libor; Trosko, James E; Bláha, Luděk; Babica, Pavel (Environmental science & technology, 2018)
Cyanotoxins microcystin-LR (MC-LR) and cylindrospermopsin (CYN) represent hazardous waterborne contaminants and potent human hepatotoxins. However, in vitro monolayer cultures of hepatic cell lines were found to recapitulate, poorly, major hepatocyte-specific functions and inadequately predict hepatotoxic effects of MC-LR and CYN. We utilized 3-dimensional (3D), scaffold-free spheroid cultures of human telomerase-immortalized adult liver stem cells HL1-hT1 to evaluate hepatotoxic potential of MC-LR and CYN. In monolayer cultures of HL1-hT1 cells, MC-LR did not induce cytotoxic effects (EC50 > 10 micromol/L), while CYN inhibited cell growth and viability (48h-96h EC50 ≈ 5.5-0.6 micromol/L). Growth and viability of small growing spheroids were inhibited by both cyanotoxins (≥0.1 micromol/L) and were associated with blebbing and disintegration at the spheroid surface. Hepatospheroid damage and viability reduction were observed also in large mature spheroids, with viability 96h-EC50 values being 0.04 micromol/L for MC-LR and 0.1 micromol/L for CYN, and No Observed Effect Concentrations <0.01 micromol/L. Spheroid cultures of adult human liver stem cells HL1-hT1 exhibit sensitivity comparable to cultures of primary hepatocytes and provide a simple, practical, and cost-effective tool, which can be effectively used in environmental and toxicological research, including assessment of hepatotoxic potential and effect-based monitoring of various samples contaminated with toxic cyanobacteria.
Keywords: Liver; bakteriální toxiny; mikrocystiny; Cyanobacteria; lidé; sinice; Stem Cells; játra; kmenové buňky; Microcystins; mořské toxiny; Marine Toxins; Bacterial Toxins; Humans